2021
DOI: 10.32942/osf.io/68as7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flotsam and jetsam: a global review of the role of inputs of marine organic matter in sandy beach ecosystems

Abstract: Sandy beaches are iconic interfaces that functionally link the ocean with the land by the flow of marine organic matter. These cross-ecosystem fluxes often comprise uprooted seagrass and dislodged macroalgae that can form substantial accumulations of detritus, termed ‘wrack’, on sandy beaches. In addition, the tissue of the carcasses of marine animals that regularly wash up on beaches form a rich food source (‘carrion’) for a diversity of scavenging animals. Here, we provide a global review of how wrack and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 172 publications
(274 reference statements)
0
3
0
Order By: Relevance
“…Changes in water level and wind speed were most extreme during storm Malik, resulting also in the largest beach wrack deposition during our monitoring period. Both wind and wave climate that influence the biogeographic patterns of beach wrack (Reimer et al, 2014;Hyndes et al, 2021) will change in the next decades and alter the beach wrack depositions patterns. Wind and wave projections for the Baltic Sea are highly uncertain due to large natural variability; but in areas no longer covered by sea ice, wind fetch and wind speeds could increase (Ahola et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in water level and wind speed were most extreme during storm Malik, resulting also in the largest beach wrack deposition during our monitoring period. Both wind and wave climate that influence the biogeographic patterns of beach wrack (Reimer et al, 2014;Hyndes et al, 2021) will change in the next decades and alter the beach wrack depositions patterns. Wind and wave projections for the Baltic Sea are highly uncertain due to large natural variability; but in areas no longer covered by sea ice, wind fetch and wind speeds could increase (Ahola et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Beach wrack increases the surface roughness and has been identified as a key factor in trapping wind-blown sand (Nordstrom et al, 2011). Furthermore, beach wrack enhances plant colonization at more seaward-located positions because it elevates the backshore and provides essential nutrients (Dugan et al, 2011;Biel et al, 2018;Hyndes et al, 2021). For Baltic coast wetlands, Ward et al (2016) have shown that already small alterations in elevation and thus inundation frequency can lead to substantial vegetation changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation